Effect of Dipyridamol, Osmolarity and Sulfhydryl Reagents on Sulphate Anion Transport in Human Erythrocytes - Pisarenko, N. A.; Bondarenko, V. A.; Ramazanov, V. V.; Koba, L. V. (Problems of Cryobiology and Cryomedicine, 2006)
The peculiarities of sulphate anion transport by band 3 protein of human erythrocyte membranes under conditions of increased medium osmolarity, modification of cytoskeletal and membrane SH-groups, as well as at dipyridamol presence in incubation medium have been studied. Dipyridamol effect on sulphate anion transport by band 3 protein of native and modified erythrocyte membrane was established to depend on its concentration in the incubation medium. At the same time the most significant reduction of anion transport is observed within the range of dipyridamol concentration from 0 to 10 Î¼M. Anion sulphate transport in hypertonic medium by band 3 protein both in native and modified erythrocytes considerably decreases if to compare with isotonic conditions. Erythrocyte treatment with iodoacetamide, p-chloromercuriobenzoic acid and their combination significantly augments sulphate transport into a cell, moreover under these conditions the highest effect of modifiers is observed during their combination.